PERBANDINGAN TINDAK PIDANA TERTENTU DALAM UNDANG-UNDANG NOMOR 1 TAHUN 1946 DENGAN UNDANG-UNDANG NOMOR 1 TAHUN 2023 DITINJAU DENGAN TEORI TUJUAN HUKUM MENURUT GUSTAV RADBRUCH - Alamsyah, Muhamad Sadam; Shobari, Ahmad; Gusma, Almabiyan; Rahmanda, Mita Riza; Antoni, Herli; Dewi, Elya Kusuma (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2023)
In realizing a Legal Purpose Proposed by Gustav Radbruch, namely Law must realize Legal Certainy, Legal Justice, and Legal Benefit every applicable law must realize a legal goal that is felt by community. Law Number 1 of 1946 concering the Criminal Code in providing Legal Certainy is still lacking due to the may doctrinal clashes in each article. And in Legal Justice provides a sense of Satisfaction, especially the justice that occurs in the community. Namely in the death penalty in serious crimes like premeditated murder. In the aspect of Legal Benefit, it provides benefits to the community to always comply and limit their behavior. But it must be followed by times. In Law Number 1 of 2023 concering the Criminal Code in realizing the objectives of law through aspect Legal certainty guarantees the concents of the article because the regulations is a product produced through the Legislative Body. In processing rights and obligations by Legal Justice, it still not felt to fulfill the sense of justice that occurs in the community, especially in death penalty with probation. Legal expediency in this Law follows the times that occur in Indonesia so that the benefits of this Law will be useful for communities in protecting their indvidual rights. Legal Reform contained in Law Number 1 Year 2023 follows the times that have occurred in Indonesian Anthropology, through several rules in terms of adultery for someone who is not yet married and respect the Living Law in society (The Living Law). Keywords: Comparison, Criminal, Purpose of Law, Gustav Radbruch.